Five-year workplace wellness intervention in the NHS - Blake, Holly; Zhou, Dingyuan; Batt, Mark E. (SAGE, 2013)
aims: Poor health and well-being has been observed among NHS staff and has become a key focus in current public health policy. The objective of this study was to deliver and evaluate a five-year employee wellness programme aimed at improving the health and well-being of employees in a large NHS workplace. method: A theory-driven multi-level ecological workplace wellness intervention was delivered including health campaigns, provision of facilities and health-promotion activities to encourage employees to make healthy lifestyle choices and sustained behaviour changes. An employee questionnaire survey was distributed at baseline (n= 1,452) and at five years (n= 1,134), including measures of physical activity, BMI, diet, self-efficacy, social support, perceived gen-eral health and mood, smoking behaviours, self-reported sickness absence, perceived work performance and job satisfaction. results: Samples were comparable at baseline and follow-up. At five years, significantly more respondents actively travelled (by walking or cycling both to work and for non-work trips) and more were active while at work. Significantly more respondents met current recommendations for physical activity at five years than at baseline. Fewer employers reported ‘lack of time’ as a barrier to being physically active following the intervention. Significantly lower sickness absence, greater job satisfaction and greater organisational commitment was reported at five years than at baseline. conclusions: Improvements in health behaviours, reductions in sickness absence and improvements in job satisfaction and organisational commitment were observed following five years of a workplace wellness intervention for NHS employees. These findings suggest that health-promoting programmes should be embedded within NHS infrastructure.